Financial institutions : national and international (Rawalpindi : Government of Pakistan, Ministry of Finance, 1964)
The author included in this book National Institutions which provide finance to trade, commerce, industry and agriculture. The role of foreign institutions have also been included. The I.B.R.D. and its affiliates, the I.F.C. and the I.D.A., are themselves major investors; but perhaps more important is the world Bank's role in co-ordinating financial investment through outfits like Aid to Pakistan Consortium. It has been felt that without an account of institutions like P.I.D.C. and A.D.Cs, though not financial institutions, the picture of overall financial operations in the sphere of industry and agriculture will remain incomplete. The materials contained in this book is largely drawn from the publications of the respective organisations.
rpm 02/05/2018
Loans
Keywords: Banks and banking; Banks and banking, International